2013
DOI: 10.1167/13.8.20
|View full text |Cite
|
Sign up to set email alerts
|

Space, color, and direction of movement: How do they affect attention?

Abstract: Paying attention improves performance, but is this improvement regardless of what we attend to? We explored the differences in performance between attending to a location and attending to a feature when perceiving global motion. Attention was first cued to one of four locations that had coherently moving dots, while the remaining three had randomly moving distracter dots. Participants then viewed a colored display, wherein the color of the coherently moving dots was cued instead of location. In the third task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In fact, the LIP feedback to MT seems to be purely spatial and makes little distinction between the different feature-selective cells in the corresponding retinotopic location (3). Human psychophysical experiments also reinforce the point that gating functions of the dorsal stream prioritise spatial locations rather than specific features (27). The different frequencies for the two functions may also be functionally fortuitous, consistent with recent evidence that the brain may use different synchronising frequencies for different functions (20).…”
Section: One Sentence Summarysupporting
confidence: 72%
“…In fact, the LIP feedback to MT seems to be purely spatial and makes little distinction between the different feature-selective cells in the corresponding retinotopic location (3). Human psychophysical experiments also reinforce the point that gating functions of the dorsal stream prioritise spatial locations rather than specific features (27). The different frequencies for the two functions may also be functionally fortuitous, consistent with recent evidence that the brain may use different synchronising frequencies for different functions (20).…”
Section: One Sentence Summarysupporting
confidence: 72%
“…Furthermore, in a motion task using both spatial and featural cues, human subjects' performance was determined more strongly by spatial attention rather than by feature‐based attention (Verghese et al. ). The concept of a strongly spatial nature of LIP output is also supported by a study that showed local inactivation of LIP leading to predominantly spatial deficits despite the presence of nonspatial modulatory signals in LIP neurons (Balan and Gottlieb ).…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in object location may be missed by a serial search dominated largely by spatially localized feedback signals, and there is human psychophysical evidence suggesting that this is indeed the case (Horowitz and Wolfe 1998). Furthermore, in a motion task using both spatial and featural cues, human subjects' performance was determined more strongly by spatial attention rather than by feature-based attention (Verghese et al 2013). The concept of a strongly spatial nature of LIP output is also supported by a study that showed local inactivation of LIP leading to predominantly spatial deficits despite the presence of nonspatial modulatory signals in LIP neurons (Balan and Gottlieb 2009).…”
Section: Role Of Lip In Top-down Selective Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, with our chosen stimuli we aim to target area MT, an Original manuscripts 66 _______________________________________________________ electrophysiologically well-described visual area, showing to be strongly influenced by attention . Other studies showed the causality between attentional deployment and linear motion discrimination (Bosworth, Petrich & Dobkins, 2012;Liu, Fuller & Carrasco, 2006;Verghese, Anderson & Vidyasagar, 2013). However, theses studies only cover two states of attention, full and poor attention.…”
Section: Introductionmentioning
confidence: 99%